Industrial training report: SWOT and Pestle Analysis / Afieka Osman Nizam - Osman Nizam, Afieka (Universiti Teknologi MARA, Perlis, 2023)
This internship report stresses on the work experience I have gathered as an Intern in the PTBI/ MXF12 department of Robert Bosch Power Tools Sdn Bhd from August 15, 2022 until February 10, 2023. In this report, I mainly have incorporated my experience at Robert Bosch Power Tools Sdn Bhd especially about my task, duties and responsibilities where I also have provided details about my 6 months’ work experience at Robert Bosch Power Tools Sdn Bhd along with a comprehensive job description where I had to work with seniors, production team and warehouse team. Not only that, I also provided the intrinsic and extrinsic benefit that I have gained from this company throughout my journey in Robert Bosch Power Tools Sdn Bhd. In this report, I have included some details about Robert Bosch Power Tools Sdn Bhd such as location, vision, mission, objective and organizational chart of my department. Then, I discussed about swot and pestle analysis of Robert Bosch Power Tools Sdn Bhd. The analysis’s objective is to help internship student to analyze a company's financial health and competitive advantages or disadvantages. In addition, I also stated my opinion from my point of view based on the SWOT Analysis that i have provided. This report will serve good information for the reader. Robert Bosch Power Tools Sdn Bhd has a good internship program.